PERAN GURU PEMBIMBING BAGI SISWA TUNAGRAHITA DALAM MENUMBUHKAN AKHLAKUL KARIMAH DI SEKOLAH INKLUSI SDN MERUYA SELATAN 06 - Safira, Dwi (Universitas Islam Darul 'Ulum Lamongan, 2024)
The research aims to understand the role played by the supervising teacher in assisting intellectually disabled students in developing noble character. This includes understanding the approaches and teaching methods used, partices of etiquette in eating and drinking in daily life, courtesy towards others and greetings both within and outside of school. The approach used in this research is qualitative and the type of research is phenomenology. Data collection techniques involve interviews and observations. Data analysis is conducted using descriptive analytics. The results of the research indicate the efforts of the supervising teacher in cultivating noble character through practices such as handshaking and greetings, etiquette in eating and drinking in daily life and the application of courtesy for both typically developing children and children with special needs.